2013
DOI: 10.1002/eji.201343668
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cells modulate T‐cell responses through TNF‐α‐mediated activation of NF‐κB

Abstract: Although mesenchymal stromal cells (MSCs) possess the capacity to modulate immune responses, little is known about the mechanisms that underpin these processes. In this study, we show that immunosupression is mediated by activation of nuclear factor kappa B (NF-κB) in human MSCs. This pathway is activated by TNF-α that is generated following TCR stimulation of T cells. Inhibition of NF-κB through silencing of IκB kinase β or the TNF-α receptor abolishes the immunosuppressive capacity of MSCs. Our data also ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 38 publications
7
72
0
Order By: Relevance
“…Moreover, we demonstrate that PPARβ/δ −/− MSCs with enhanced immunosuppressive capacities display a significantly higher NF-κB activity both at steady state and upon activation with proinflammatory cytokines. This is consistent with the inhibitory action of PPARs on NF-κB signalling pathways described in immune cells that is associated with their anti-inflammatory properties2 and the TNF-α-mediated NF-κB activation involved in the immunomodulatory activity of MSCs 34. In this latter study, the authors described that the impairment of NF-κB activation antagonises the inhibitory effect of MSCs on T cell proliferation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, we demonstrate that PPARβ/δ −/− MSCs with enhanced immunosuppressive capacities display a significantly higher NF-κB activity both at steady state and upon activation with proinflammatory cytokines. This is consistent with the inhibitory action of PPARs on NF-κB signalling pathways described in immune cells that is associated with their anti-inflammatory properties2 and the TNF-α-mediated NF-κB activation involved in the immunomodulatory activity of MSCs 34. In this latter study, the authors described that the impairment of NF-κB activation antagonises the inhibitory effect of MSCs on T cell proliferation.…”
Section: Discussionsupporting
confidence: 82%
“…Since PPARβ/δ acts as a negative regulator of NF-κB activity,2 and that immunosuppression is mediated by activation of NF-κB in MSCs,34 we examined the activity of NF-κB in both PPARβ/δ +/+ and PPARβ/δ −/− MSCs. Using the luciferase-based reporter system, we demonstrated that PPARβ/δ −/− MSCs displayed a significantly higher NF-κB activity than PPARβ/δ +/+ MSCs (figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggest that lower expression of CXCR4 by MSCs lead to the failure of these cells to migrate into inflammation site and consequent loss of immunoregulatory functions [175]. Also, other authors showed that TNF- α released by activated T-cells confers immunoregulatory properties upon MSCs by binding to TNF-receptor 1 (TNF-R1) and activating the nuclear factor kappa B (NF- κ B) pathway [176, 177], contrasting with other studies, in which INF- γ seems to be a required factor. Besides, the presence of APRIL and BAFF—two TNF family proteins—is able to modulate the functionality of MSCs through activation of extracellular signal-regulated kinases 1/2 (ERK1/2) and Akt kinases.…”
Section: Mesenchymal Stromal Cells “Activation”mentioning
confidence: 99%
“…IFN-g can trigger the proliferation and immunomodulatory function of MSCs via the Kynurenine-dependent mechanism [43]. Likewise, TNF-a induces the proliferation and immunosuppressive function of MSCs using the NF-kb pathway [44]. Thus, NK cells and T-lymphocytes are linked to the licensing of MSCs as major sources of TNF-a that is highly expressed during both inflammatory and repair phases [45].…”
Section: Preparation For the Repair Phase; Licensing Of Mscsmentioning
confidence: 99%